Penyusunan Program Ngapel oleh Iprahumas Indonesia - Muhamad Handar (Jurnal Riset Public Relations, 2022)
Abstract. This study aims to determine the preparation of the NGAPEL program implemented by Iprahumas Indonesia. In its realization in accordance with Law no. 14 of 2008 concerning Openness of Public Information, Iprahumas Indonesia as a government public relations officer functions to provide education and information to the public. The research method used is qualitative. The tools used are observation, documentation, interviews, and literature conducted on informants and key informants in Iprahumas Indonesia. The data obtained was immediately compiled and analyzed so that it became a descriptive data. The results obtained are that the NGAPEL live program on IG TV Iprahumas can share information related to many things and information both in the nature of entertainment, information and education whose scope is in the public sphere or the wider community, the topic of conversation is adjusted to the current conditions, neutral and transparent. The conclusion of this study is that the NGAPEL Iprahumas Indonesia program has become a vehicle for information education in the field of public relations in a practical way in implementing the values ​​of the NGAPEL program as Iprahumas Indonesia's vision, "increasing the capacity of Public Relations Pranata as a career and professional path: developing a dynamic professional organization of Public Relations Pranata and adaptive to the dynamics of society.” Abstrak. Penelitian ini bertujuan untuk mengetahui penyusunan program NGAPEL yang diterapkan Iprahumas Indonesia. Dalam perwujudannya sesuai dengan UU No. 14 Tahun 2008 tentang Keterbukaan Informasi Publik, Iprahumas Indonesia sebagai humas pemerintah berfungsi untuk memberikan edukasi dan informasi kepada publik. Metode penelitian yang digunakan adalah kualitatif. Alat yang digunakan adalah observasi, dokumentasi, wawancara, dan kepustakaan yang dilakukan kepada informan dan key informant yang ada di Iprahumas Indonesia. Data yang diperoleh langsung disusun dan dianalisis sehingga menjadi sebuah data deskriptif. Hasil yang diperoleh adalah program live NGAPEL di IG TV Iprahumas dapat saling sharing informasi terkait banyak hal dan informasi baik yang bersifat entertaintment, informasi maupun edukasi yang cakupannya ke ranah publik atau masyarakat luas, topik perbincangan pun disesuaikan dengan kondisi yang sekarang terjadi, bersifat netral dan transparan. Kesimpulan dari penelitian ini adalah program NGAPEL Iprahumas Indonesia telah menjadi wahana edukasi informasi di bidang kehumasan secara praktis dalam mengimplementasikan nilai-nilai program NGAPEL sebagaimana visi Iprahumas Indonesia, “meningkatkan kapasitas Pranata Humas sebagai jenjang karir dan profesi: mengembangkan kelembagaan organisasi profesi Pranata Humas yang dinamis dan adaptif terhadap dinamika masyarakat.”